A prospective study of fetomaternal outcome in patients of pregnancy with jaundice in tertiary care centre - Arora, Monica; Verma, Suniti; Desai, Ranjana; Sehra, Ram Narain (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The objective of the study was to study the incidence of jaundice, biochemical alterations, Fetomaternal outcome and various liver pathologies of pregnant patients with jaundice. Methods: This was a prospective observational study conducted in Dr S N Medical College Jodhpur, Rajasthan, India from June 2014 to February 2016. Total fifty pregnant patients with clinical jaundice and prodromal symptoms of hepatitis were included in study. Results: Out of 40,398 deliveries in our hospital, 50 cases of jaundice were identified giving an incidence of 1 in 808 (0.12%). Most common cause of jaundice in pregnancy in our set up was viral hepatitis i.e. 13 cases (26%) were HEV+ and 1 case (2%) came out to be HAV+. Serum LDH levels were raised in 36% of patients. Maximum no. of patients had their serum AST/ALT levels in the range of 100-1000 IU/ml (54%). Out of 52 births (2 twins) 34 were live births (65.38%) and rest were either SB or IUFDs. Most common causes of mortality in patients were Septicemia, MODS, DIC (25%) followed by HELLP syndrome and HEV+ viral hepatitis equally (16.67%). Maximum no. of patients with jaundice suffered from postpartum haemorrage and septicemia (60%). Conclusions: Most common cause of jaundice in pregnancy in our study was viral hepatitis. Public awareness about the various routs of transmission of different types of infective hepatitis, improving sanitary conditions and habits, health education of preventive measures can help in reducing the burden of jaundice in pregnancy.